Integrasi Teknologi Baru dalam Meningkatkan Pendidikan Islam di Indonesia - Suci Hartati; Muhammad Feri Fernadi; Esen Pramudya Utama (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
Islamic Studies teachers face challenging challenges Based on the understanding that the duties and responsibilities of religious teachers are more than onerous, globalization which has become part of people's lives causes difficulties for teachers. Challenges for teachers today are different from the past. It is necessary that we do a lot in the form of skills and strategies to ensure that teachers are always in their best role. There is a need for a variety of instructional approaches, methods, and course materials in the field of Islamic Studies. Among these are aqidah (Islamic beliefs), sabi'ah (Islamic ethics), fiqh (Islamic law), the Koran, and Islamic history. With this in mind, it was necessary for the author to research and articulate this research in order to spend a lot of time in class using the